Christians are hate-filled hypocrites-- and other lies you've been told [a sociologist shatters myths from the secular and Christian media] - Wright, Bradley R. Entner (Carol Stream, IL : Oasis Audio, 2010)
"A research sociologist uses statistics to reveal the state of the Evangelical Church, showing that the church is in better shape than the secular and Christian media claims"--Provided by publisher.
Subtitle from container.
Unabridged.
In container (14 x 17 cm.).
Compact disc.
Read by the author.
Keywords: Evangelicalism -- United States; Christianity -- United States; Christianity -- Controversial literature; Mass media in religion -- United States